Glutamate (mGluR-5) gene expression in brain regions of streptozotocin induced diabetic rats as a function of age: role in regulation of calcium release from the pancreatic islets in vitro - Balakrishnan, Savitha (BioMed Central, 2009)
Metabotrophic glutamate receptors (mGluRs) modulate cellular activities involved in the processes of differentiation and degeneration. In this study, we have analysed the expression pattern of group-I metabotropic glutamate receptor (mGlu-5) in cerebral cortex, corpus striatum, brainstem and hippocampus of streptozotocin induced and insulin treated diabetic rats (D+I) as a function of age. Also, the functional role of glutamate receptors in intra cellular calcium release from the pancreatic islets was studied in vitro. The gene expression studies showed that mGlu-5 mRNA in the cerebral cortex increased siginficantly in 7 weeks old diabetic rats whereas decreased expression was observed in brainstem, corpus striatum and hippocampus when compared to control. 90 weeks old diabetic rats showed decreased expression in cerebral cortex, corpus striatum and hippocampus whereas in brainstem the expression increased significantly compared to their respective controls. In 7 weeks old D+I group, mGlu-5 mRNA expression was significantly decreased in cerebral cortex and corpus striatum whereas the expression increased significantly in brainstem and hippocampus. 90 weeks old D+I group showed an increased expression in cerebral cortex, while it was decreased significantly in corpus striatum, brainstem and hippocampus compared to their respective controls. In vitro studies showed that glutamate at lower concentration (10(-7 )M) stimulated calcium release from the pancreatic islets. Our results suggest that mGlu-5 receptors have differential expression in brain regions of diabetes and D+I groups as a function of age. This will have clinical significance in management of degeneration in brain function and memory enhancement through glutamate receptors. Also, the regulatory role of glutamate receptors in calcium release has immense therapeutic application in insulin secretion and function.